Partisipasi Anggota Kelompok Tani Tasatoma Pada Usahatani Padi Sawah Di Kelurahan Woloan Satu Utara Kecamatan Tomohon Barat - Montolalu, Mega Putri Hetvika; Lolowang, Tommy Ferdy; Ngangi, Charles Reijnaldo (Sam Ratulangi University, 2023)
The purpose of this study was to find out how the participation of members of the Tasatoma farmer group is in rice farming in Woloan Satu Utara Village, West Tomohon District, Tomohon City. This research was conducted for 3 months, starting from May to July 2023. The research site was carried out by the Tasatoma Farmers Group in Woloan Satu Utara Village, West Tomohon District, Tomohon City. The types of data taken in this research are primary data and secondary data. Primary data was data taken by researchers in the field directly from the source, namely the management and members of the Tasatoma farmer group who were the research sample using a list of questions that had been prepared by the researcher, with a total of 14 respondents. The results showed that the participation of members of the Tasatoma farmer group was 75.89% meaning that in general the participation was classified as less active when carrying out activities in the farmer group. This shows that as a whole the members of the Tasatoma farmer group still play an active role even though there are 2 indicators that must be considered and improved, especially on the respondent indicator in giving input to meetings in the planning stage and respondents in giving input to meetings in the evaluation stage, respondents must further improve self-confidence, innovation, as well as broad thinking so that when asked to submit suggestions or input, respondents can do so and there are interactions that occur at meetings in the planning stage as well as meetings in the evaluation stage.